2005
DOI: 10.1177/154405910508401210
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 4 Pulpotomy Techniques—Randomized Controlled Trial

Abstract: Pulpotomy is the accepted therapy for the management of cariously exposed pulps in symptom-free primary molars; however, evidence is lacking about the most appropriate technique. The aim of this study was to compare the relative effectiveness of the Er:YAG laser, calcium hydroxide, and ferric sulfate techniques with that of dilute formocresol in retaining such molars symptom-free. Two hundred primary molars in 107 healthy children were included and randomly allocated to one of the techniques. The treated teeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
98
2
27

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(144 citation statements)
references
References 18 publications
14
98
2
27
Order By: Relevance
“…Similar to our study, in their researches assessing the clinical success rate of amputations with FS; Fei et al [20] observed a 100% success rate at the end of 12 months, Markovic et al [21] observed 89% at the end of 18 months, and Huth et al [22] observed 100% at the end of 24 months.…”
Section: International Journal Of Dental Sciences and Researchsupporting
confidence: 78%
“…Similar to our study, in their researches assessing the clinical success rate of amputations with FS; Fei et al [20] observed a 100% success rate at the end of 12 months, Markovic et al [21] observed 89% at the end of 18 months, and Huth et al [22] observed 100% at the end of 24 months.…”
Section: International Journal Of Dental Sciences and Researchsupporting
confidence: 78%
“…[1][2][3][4][5][6][7] Basically, this technique consists of removing the coronal pulp and maintaining the vitality of the radicular pulp. The purpose is to remove the bacterial infection leaving the treated tooth asymptomatic until its exfoliation.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose is to remove the bacterial infection leaving the treated tooth asymptomatic until its exfoliation. [3][4][5][6][7] Medicaments applied to radicular pulp tissue after pulpotomy have included formocresol, 1,3,4 ferric sulphate, 3,4 calcium hydroxide 4 and mineral trioxide aggregate (MTA). 1,[8][9][10][11][12][13][14] Objective This study compared the clinical and radiographic effectiveness of mineral trioxide aggregate (MTA) and Portland cement (PC) as pulp dressing agents in carious primary teeth.…”
Section: Introductionmentioning
confidence: 99%
“…If the stimulus or damage is severe, the pulp healing capacity may be exceeded and it may progress to an irreversibly inflamed condition and to necrosis. However, if pulp exposure is discrete in primary or young permanent teeth, some procedures may be performed in an attempt to reestablish pulpal health and maintain its vitality (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Pulpotomy comprises coronal pulp amputation and placement of a protective agent over the remaining viable root pulp in order to preserve its vitality and function (2,3). It is indicated for primary or young permanent teeth with inflamed and/or infected coronal pulp.…”
Section: Introductionmentioning
confidence: 99%